Online IELTS (International English Language Testing System) Training for High School Teachers as Preparation for Applying for Foreign Scholarships - Andri Suherman; Hamzani Wathoni; M Adib Nazri (Universitas Lambung Mangkurat, 2024)
IELTS is a mandatory requirement in applying for overseas master's degree scholarships. However, many people, including senior and vocational high school teachers in Selong City, East Lombok, face difficulty answering IELTS questions. Other than having no educational background in the English Language, they also have no time to take IELTS courses because of their heavy workload. Therefore, this community service activity aims to provide IELTS training to high school teachers in Selong City, East Lombok. This IELTS training is expected to help them meet the IELTS score when applying for overseas scholarships. Twenty teachers participated in this IELTS training, which was held in August 2023. Data from the pre-test and post-test revealed that the participants showed increased IELTS scores, although insignificant. Besides, data obtained from the online questionnaire and interview session showed that the participants positively responded to this IELTS training.